Homework 01 and 02 Partial Solutions

# Homework 01 and 02 Partial Solutions - Partial Solutions...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Partial Solutions and Comments, Math 74 HW2 and HW3 General Comments: Please split up your proofs into paragraphs when appropriate, such as in longer proofs like HW3, Problem 9. Also, you should define most objects that you’re using, though you don’t need to state what Z , N , ∅ , etc. are. 2.1a. ∀ ε > ∃ δ > ∀ x ∈ R ( | x- a | < δ = ⇒ | f ( x )- f ( a ) | < ε ). 2.1b. ∃ ε > ∀ δ > ∃ x ∈ R ( | x- a | > δ ∧| f ( x )- f ( a ) | ≥ ε ). 2.2. Comment: The problem asked to translate the given statements into other statements , not sets . Some possible solutions: a. ( ∀ x )( x ∈ A = ⇒ x ∈ B ) ⇔ A ⊆ B . b. ( ∀ x )( x ∈ A ⇔ x ∈ B ) ⇔ A = B . c. ( ∀ x )( x / ∈ A ) ⇔ A = ∅ . d. ( ∃ x )( x / ∈ A ∧ x ∈ B ) ⇔ A B , or A C ∩ B = ∅ . 2.7. Proposition. Let g ◦ f be injective. Then f is injective. Comment: g ◦ f being injective does not imply that g is injective. Let f : N → R be f ( n ) = n and g : R → R be g ( x ) = x 2 . Proof. Assume g ◦ f is injective and suppose f ( x ) = f ( y ). Then g ( f ( x )) = g ( f ( y )), which is equivalent to g ◦ f ( x ) = g ◦ f ( y ). Since g ◦ f is injective,...
View Full Document

## This note was uploaded on 05/04/2011 for the course MATH 73 taught by Professor Danberwick during the Spring '09 term at Berkeley.

### Page1 / 3

Homework 01 and 02 Partial Solutions - Partial Solutions...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online